2020
DOI: 10.1002/ijfe.2312
|View full text |Cite
|
Sign up to set email alerts
|

The performance of UK stock recommendation revisions: Does brokerage house reputation matter?

Abstract: Our study examines the impact of brokerage house (BH) reputation on the performance of investment strategies following stock recommendation revisions in the UK stock market. We develop two alternative proxies for BH reputation based either on the past positions on the annual Institutional Investor (II) All-Europe Research Team or on the past recommendation performance of BHs.We find that BH reputation proxied by the past II rankings has no significant impact on the recommendation performance, suggesting that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 55 publications
0
1
0
Order By: Relevance
“…Kudryavtsev (2021), as a result of the analysis of the correlation between stock returns before and after analyst recommendation revisions for stocks traded on NYSE, AMEX, and NASDAQ, found that an advisory revision for a particular stock caused the stock price to move toward the opposite direction and concluded that it might have indicated that the underlying information was not sufficiently included in the stock price if it occurred after a short period. In their study where they examined the impact of brokerage company reputation on the performance of investment strategies following stock recommendation revisions in the UK stock market, Su et al (2020) concluded that the reputation of the brokerage house had a significant impact on the recommendation performance based on the "European Research Team Institutional Investor Positions" or the past recommendation performance of brokerage houses, however, it was also found that the performance of the investment recommendation given by the brokerage houses in the previous year had a significant positive impact on the recommendation performance of the next year. It concluded that the recommendation performance in the UK stock markets was permanent.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Kudryavtsev (2021), as a result of the analysis of the correlation between stock returns before and after analyst recommendation revisions for stocks traded on NYSE, AMEX, and NASDAQ, found that an advisory revision for a particular stock caused the stock price to move toward the opposite direction and concluded that it might have indicated that the underlying information was not sufficiently included in the stock price if it occurred after a short period. In their study where they examined the impact of brokerage company reputation on the performance of investment strategies following stock recommendation revisions in the UK stock market, Su et al (2020) concluded that the reputation of the brokerage house had a significant impact on the recommendation performance based on the "European Research Team Institutional Investor Positions" or the past recommendation performance of brokerage houses, however, it was also found that the performance of the investment recommendation given by the brokerage houses in the previous year had a significant positive impact on the recommendation performance of the next year. It concluded that the recommendation performance in the UK stock markets was permanent.…”
Section: Literature Reviewmentioning
confidence: 99%